Normative Review of Judge's Decision About Interfaith Marriage in Indonesia - Maiyori, Cisilia; Akbarizan (JAWI : Journal of Ahkam Wa Iqtishad, 2025)
The development of the times in the form of developments in human thought patterns and developments in technology has influenced various aspects of life. This development problem also affects the smallest structure of society in Indonesia, namely the family. Patterns of behavior in marriage, family relationships and wealth issues are issues that trigger conflicts in religious courts. There are many groups of people who adhere to human rights who want freedom in all matters, influencing the rules in family law. Likewise with regard to marriage, free flow people want the freedom to choose anyone, and marry people of different religions on the basis of a form of love and affection. So interfaith couples emerge who want to be legalized by Indonesian law.                The purpose of this scientific work in the form of an article is to find out things related to interfaith marriages, in terms of prohibiting regulations, the dualism of court decisions regarding whether or not it is permissible to marry people of different faiths, by analyzing various judges' decisions regarding interfaith marriages. The method used is a normative legal research method by analyzing legal sources, in this case the judge's decision which is the basis for consideration of decisions made by different religions. It is hoped that the results of this research can be a contribution to national law-forming bodies to improve existing regulations so that legal certainty is achieved.